Keefektifan Penggunaan Teknik Kata Kunci terhadap Keterampilan Menulis Puisi Epigram Berbasis Pendidikan Karakter - Haerunisyah, Haerunisyah; Usman, Usman (Nuances of Indonesian Language, 2023)
This study aims to: (1) describe the skills of epigram poetry writing based on character education for class X students of SMA Negeri 2 Lambu West Nusa Tenggara befero using the keyword/1technique; (2) describe nthe skills of epigram poetry writing based on character education for class X students of SMA Negeri 2 Lambu West Nusa Tenggara after using the keyword/1technique; (3) to determine the effectiveness of character education on the epigram poetry writing skills based on character education for class X students of SMA Negeri 2 Lambu West Nusa Tenggara.This type of research is quantitative research. The research population was class X students of SMA Negeri 2 Lambu. The sample of this research was students of class X IPA 1. The data collection technique used was pretest and posttest. The pretest results show an average value of 62.50 and the posttest results show an average value of 77.92. Based on data analysis using the Paired Sample Test, the value of Sig. namely 0.000 <0.05, then H0 is rejected and H1 is accepted. Therefore, it can be concluded that the keyword technique is effectively applied in learning to write epigram poetry based on character education for class X SMA Negeri 2 Lambu, West Nusa Tenggara.